2021
DOI: 10.5194/soil-2021-113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transition to conservation agriculture: how tillage intensity and covering affect soil physical parameters

Abstract: Abstract. Conservation agriculture (CA) relies on two key practices to improve agricultural sustainability—reduced tillage and cover crop usage. Despite known soil physics benefits (reduced soil compaction and strength, enhanced soil porosity and permeability), inconsistent reports on short-term CA results have limited its adoption in European agroecosystems. To elucidate the short-term effects, a three-year experiment in the low-lying Venetian plain (Northern Italy) was undertaken. Bulk density, penetration r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The data of the European Conservation Tillage Federation (2017) about CA showed that only 5 % of the agricultural land in the 27 th members of the EU was under some of the elements of the conservational tillage technology, but the NT was applied scarcely (3.44 %) on the agricultural lands (Table 1). The availability of discrepancies in the results of short-term experiments related to the adoption of CA and due to unrealistically short time-frame for achieving the expected outcomes also could be considered as reasons restraining the adoption of CA in the agroecosystems in Europe (Mitchel et al, 2019, Sartori et al, 2022.…”
Section: The Adoption Of Ca and Nt On A Global Scalementioning
confidence: 99%
“…The data of the European Conservation Tillage Federation (2017) about CA showed that only 5 % of the agricultural land in the 27 th members of the EU was under some of the elements of the conservational tillage technology, but the NT was applied scarcely (3.44 %) on the agricultural lands (Table 1). The availability of discrepancies in the results of short-term experiments related to the adoption of CA and due to unrealistically short time-frame for achieving the expected outcomes also could be considered as reasons restraining the adoption of CA in the agroecosystems in Europe (Mitchel et al, 2019, Sartori et al, 2022.…”
Section: The Adoption Of Ca and Nt On A Global Scalementioning
confidence: 99%
“…Conservation agriculture (CA) and other soil management strategies implying a reduction of tillage have been reported to reduce soil degradation -preserving soil structure and associated porosity -in different agroecological situations (Verhulst et al, 2010;Sartori et al, 2022), and in many cases they are indeed designed for this purpose (Virto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, while tillage reduction or cessation seems to alleviate the negative effects on soil structure and topsoil SOM, it also removes some of its beneficial effects especially in the short term. Kay and Vanden-Bygaart (2002) and Sartori et al (2022) speculated that in the short term, soil compaction would be expected as a result of tillage absence and traffic load, while crop yield and soil structure stabilization are expected in the mid and long term (> 15 years) (Rusinamhodzi et al, 2011) as a result of greater biological activity and SOM redistribution.…”
Section: Introductionmentioning
confidence: 99%